Key Indicators of Financial Ratios on Value of Food and Beverage Companies in Indonesia - Faizul Mubarok; Muhammad Ridho Syakhran Siregar (LP3M Universitas Putra Bangsa, 2022)
The country earns substantial foreign exchange from the food and beverage sector, the primary sector for people's needs. This study aims to analyze the effect of debt to equity ratio (DER), return on assets (ROA), free cash flow (FCF), and growth (GRW). This study uses five companies in the food and beverage sector from 2015 to 2019 with quarterly financial reports. The study results using the fixed-effect model prove that all the variables studied significantly affect the price to book value. Companies need to maintain and improve their business performance and financial performance, then report them following the principles and standards that apply to each period's financial statements to attract investors.